Geometric anisotropy on biomaterials surface for vascular scaffold design: engineering and biological advances. (3rd June 2019) - Wang, Zuyong; Zhang, Wanqi; Xie, Chao; Wen, Feng; Ma, Chao; Lin, Nan; Thian, Eng San; Wang, Xianwei
Abstract: Scaffold designs in combination with drug, growth factor and other bioactive chemicals account for lasting progress of vascular tissue engineering in the past decades. It is a great achievement to adjust tissue matrix composition and cell behaviour effectively. However, regenerating the innate physiologies of a blood vessel still needs its precise architecture to supply the vessel with structural basis for vascular functionality. Recent developments in biomaterial engineering have been explored in designing anisotropic surface geometries, and in turn to direct biological effects for recapitulating vascular tissue architecture. Here, we present current efforts, and propose future perspectives for the guidance on the architectural reconstruction and scaffold design of blood vessel.